ACRITICAL REVIEW OF RESEARCH ON NEGOTIATION OF MEANING INSECOND LANGUAGE LEARNING - Rudi Hartono (Global Expert: Jurnal Bahasa dan Sastra, 2017)
Negotiation of meaning is generally defined as conversational modifications or adjustments that take place in communicative interactions when learners and their interlocutors experience difficulty in understanding messages. In a conversation, a speaker may employ a communication strategy to communicate effectively using negotiation of meaning. There is a need to examine the impact of negotiation for meaning in classroom interaction and the extent to which negotiation of meaning contribute to L2 learning. This paper reports on a critical review of research conducted on negotiation of meaning strategies used by second language learners in EFL/ESL contexts. Thispaper specifically discusses the ways in which learners of English employ negotiation of meaning strategies in conversation in the studies reviewed. This paper focuses on the functions of negotiation of meaning strategies. This paper concludes by addressing pedagogical implication of negotiation of meaning in second language classrooms. Key words : negotiation of meaning strategies, second language learning,conversation